2018
DOI: 10.1021/acs.organomet.8b00470
|View full text |Cite
|
Sign up to set email alerts
|

Structure–Function Relationship in Ester Hydrogenation Catalyzed by Ruthenium CNN-Pincer Complexes

Abstract: A series of six pincer–ruthenium complexes has been synthesized and applied in the catalytic hydrogenation of esters. The ruthenium complexes have the formula Ru­(pincer)­HCl­(CO), where the CNN-pincer ligands feature N-heterocyclic carbene (NHC), pyridine, and dialkylamino donor groups. Through systematic variation of the steric bulk of the NHC substituent and the amine substituents, a clear structure–function relationship emerges. The most active catalysts in this series feature the bulkiest NHC substituent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 95 publications
0
16
0
Order By: Relevance
“…Chianese and co‐workers reported the synthesis of a series of Ru pincer complexes 87 (Scheme 29). [44] It should be particularly noted that AgCl was employed in aiming to assist the complete dissociation of PPh 3 , as AgCl is known to react with PPh 3 to form Ag 4 Cl 4 (PPh 3 ) 4 [45] . These Ru II pincer complexes, together with their analogs earlier reported by the same group, were tested for their activity in catalytic ester hydrogenation reactions (Scheme 29).…”
Section: Nhc Employed As An Arm Donormentioning
confidence: 99%
“…Chianese and co‐workers reported the synthesis of a series of Ru pincer complexes 87 (Scheme 29). [44] It should be particularly noted that AgCl was employed in aiming to assist the complete dissociation of PPh 3 , as AgCl is known to react with PPh 3 to form Ag 4 Cl 4 (PPh 3 ) 4 [45] . These Ru II pincer complexes, together with their analogs earlier reported by the same group, were tested for their activity in catalytic ester hydrogenation reactions (Scheme 29).…”
Section: Nhc Employed As An Arm Donormentioning
confidence: 99%
“…We have reported a series of CNN–pincer ruthenium catalysts for ester hydrogenation, which differs from those of Song and Sánchez in that the pyridine and NHC rings are directly linked, so that the only available site for ligand deprotonation is the CH 2 linker between the pyridine and NR 2 groups . A detailed study of the effect of ligand structure on catalyst activity showed that activity increased with increasing steric bulk on the NHC substituent . A striking effect of the amine substituent was also observed, as NEt 2 or N i Pr 2 groups gave high activity while an NMe 2 group led to greatly diminished activity.…”
Section: Introductionmentioning
confidence: 60%
“…The CNN–Ru precursors to the rearranged, CC-chelated complexes described above form catalysts for ester hydrogenation upon activation with NaO t Bu. , Our previous ester hydrogenation experiments were conducted at 105 °C, while the CNN-to-CC ligand rearrangements occur at room temperature. Although phosphine ligands were not added to catalytic reactions in our previous work, it is plausible that a similar ligand rearrangement occurs during catalysis, potentially as a pathway for activation or deactivation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations